Penyuluhan Perencanan dan Pengelolaan Keuangan dalam Berwirausaha - SMK BISTEK Gunungsindur Bogor - Jumino Jumino; Edi Mulyanto; Tutug Srijatmiko (Pekodimas : Jurnal Pengabdian Kepada Masyarakat, 2023)
This PKM is more focused on how to plan and manage finances, because in business financial factors should not be ruled out, the risks that will be generated can be fatal or very high and can threaten bankruptcy / not running the business if it is not supported by professional and accountable management in entrepreneurship . Therefore, you have to start getting to know the calculation of Estimated Income, the costs needed in the business, Cash Flow in and out (Cash Flow), capital or funds owned and where the source of financing comes from. It is hoped that the participants must understand and understand how important this financial problem is in Entrepreneurship, how to: Financial Ratio Analysis in planning, Techniques for using financial reports, Cash Flow techniques and approaches, Techniques and approaches to evaluating capital budgets, all of which must be studied. carried out to mitigate risks in entrepreneurship, in addition to aspects of legality, marketing strategy, operational management and others. Keywords: Planning, Management, Finance, Entrepreneurship